Analysis of the pattern for physical development of desert cities by the prospective approach: A case study of the city of Yazd - Mohhammad Rasoli; Mina Shirmohhamadi (کاوش‌های جغرافیایی مناطق بیابانی, 2020)
Accelerated urbanization of cities and their limited capacity have made it increasingly necessary to focus on scenario writing for the purpose of urban physical development. In this regard, the present study aims to explain the physical development pattern in the city of Yazd with a prospective approach. It seeks to steer the city's development process in the right direction. In terms of purpose, the study is an applied one, and, in terms of data collection, it is descriptive-analytical. In order to investigate the physical development of Yazd through the Holderen model and the McMake software, the effective indicators have been identified in the development process of the city. Finally, in order to predict the possible physical development status of Yazd up to 2031, the key factors were analyzed in the wizard scenario software. As the results of the research show, based on the calculations in the Holderen model, about 39.83 percent of the city growth occurred from 1977 to 2017 due to the horizontal growth of the city, and about 60. 16 percent of the development was due to the population growth. The key factors in the wizard scenario software represent three types of scenarios including four strong scenarios, 158 weak scenarios and 16 possible scenarios. The possible scenarios with 128 states are in three situation including optimal, static, and critical conditions. Of these, the optimal situation with 10 states is identified as the most likely one for the future of Yazd physical development.